Global Positioning System and Forestry Applications - Erdem, Ramazan; Erdin, Kadir (Zenodo, 2023)
With the developing technology, the use of GPS in forestry has become widespread and compulsory. Positional data are important in the processing and evaluation of data. The importance of global positioning systems developed to collect spatial data on satellite basis increases. Today, with the developing technology, there have been developments in GPS systems. Therefore, GPS systems have provided great convenience in map production. It is of great importance, especially since it provides an alternative to forestry works with large and difficult working conditions and is a less time-consuming and economical method in terrestrial measurements compared to other measuring devices. In this study, it is aimed to make a general evaluation about global positioning system and its use in forestry applications.
Keywords: forestry measurements; GPS; forestry measurements, DGPS; 15. Life on land